Proportion of WaterBorne Diseases in Children Aged 0 To 5 Years in the Health Area of the Urban Dispensary in Ebolowa - Cameroon - Nana Pamela; P M Tebeu; H Ngouakam; Takougang I; Fouedjio H; Boukou J C; Woromogo H; Nebardoum D; Jesse A; Mbicka C; Kitembo Ja; Mbongo Ja (Journal of Public Health International, 2021)
Background Water-related diseases are water-related disorders of the body. They are a public health problem as they are responsible for 60% of infant mortality in our developing countries. There are few studies in South Cameroon on the subject. Overall Objective of this work was to study the explanatory behavioral factors of waterborne diseases in children aged 0 to 5 years in the health area of the urban dispensary in Ebolowa in Cameroon in 2020. Methodology This was an analytical cross-sectional study comparing two groups of children (group 1: children affected by waterborne diseases group 2: children unaffected by waterborne diseases) within the health area of the Ebolowa urban area. It lasted 21 months and the study period was from 28 December 2020 to 22 January 2021. We included children aged 0 to 5 years present in households where parents/guardians gave their informed consent. Sampling was probabilistic and cluster sampling. Using the Kelsey formula, we obtained a sample of 420 households and 566 children. Data was collected using a questionnaire and stored in the Excel spreadsheet and analyzed with CDC USA's epi info software 7.2.2.6. The calculation p value was done with Stat Calc at the significance threshold of 0.05. Bold The proportion of waterborne diseases was 97% (549/566) among the children aged 0 to 5 years surveyed. The most common reasons for using the health service for children aged 0-5 years were diarrhea 78.62% (IC75.06-81.80), and malaria 78.09% (74.09-81.30). The median age of children suffering from these pathologies was 36 months (24; 60). The gender ratio (Boys/Girls) was 2.06/1. Conclusion We propose to increase the awareness of mothers/guardians on good practices; also, to increase health promotion in the fight against waterborne diseases.
Keywords: Proportion